Comparison of Mathematics Learning Outcomes with Student Team Achievement Divisions and Team Assisted Individualization Model - Jitu Halomoan Lumbantoruan; Gerneke Dane; Bradley Mahyar (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2022)
The purpose of this study was to determine the difference between student learning outcomes in mathematics using the Student Team Achievement Divisions (STAD) learning model and the Team Assisted Individualization (TAI) learning model. The research method is descriptive quantitative with a quasi-experimental approach, and a two-group posttest only control design. Samples were taken by means of convenience sampling. The data collection technique is a test instrument by looking at the learning outcomes. The results and findings, based on the results of hypothesis testing using the t-test, obtained that t count is greater than t table of 3.179> 1.995 with a significance level of 0.05. These findings are supported by the calculation of learning outcomes for experimental class I using the Student Team Achievement Divisions method with the average value is 70.01, this shows a higher value than the experimental class II which uses the Team Assisted Individualization method which averages 66.90. The conclusion is that there are differences in the learning outcomes of students who are taught using the Student Team Achievement Divisions model with students who are taught using the Team Assisted Individualization learning model. The Student Team Achievement Divisions learning model produces higher learning outcomes and is recommended to be used in teaching all mathematics materials at all levels